PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 43 MERANGIN - Mutmainah; Hidayati Rais; Awatif (Hira Institute, 2024)
This research was motivated by a lack of understanding of mathematical concepts among students. Students have not been able to meet the indicators of understanding mathematical concepts. The aim of this research is to find out whether students who study using the Talking Stick cooperative learning model understand mathematical concepts more thoroughly than students who study using the conventional learning model for class IX students at SMP 43 Merangin. This research used experimental methodology and a quantitative approach, using a sample of 102 class IX students of SMP 43 Merangin who were divided into 4 classes. Simple Random Sampling is the method used for sampling. Essay-style questions are used as a means of collecting data on students' understanding of mathematical concepts. The t test is a data analysis technique used to test hypotheses because it is known that the data has a homogeneous variance and is normally distributed based on the results of testing the analysis requirements. Hypothesis test results are obtained and . Because or 1,676 then accepted. From these results, it was concluded that the understanding of mathematical concepts using the Talking Stick type cooperative learning model was superior compared to using conventional learning for class IX students at SMP Negeri 43 Merangin.